Expression and Clinical Significance of High‐Mobility Group AT‐hook 2 (HMGA2) in Osteosarcoma. Issue 5 (7th April 2022) - Cui, Juncheng; Dean, Dylan; Hornicek, Francis J; Yi, Guoliang; Duan, Zhenfeng
Abstract : Objective: Although high‐mobility group AT‐hook 2 (HMGA2) has been shown to have crucial roles in the pathogenesis and metastasis of various malignancies, its expression and significance in osteosarcoma remain unknown. Here we evaluate the expression, clinical prognostic value, and overall function of HMGA2 in osteosarcoma. Methods: Sixty‐nine osteosarcoma patient specimens within a tissue microarray (TMA) were analyzed by immunohistochemistry for HMGA2 expression. Demographics and clinicopathological information including age, gender, tumor location, metastasis, recurrence, chemotherapy response, follow‐up time, and disease status were also collected. After validation of expression, we determined whether there was a correlation between HMGA2 expression and patient clinicopathology. HMGA2 expression was also evaluated in osteosarcoma cell lines and patient tissues by Western blot, we analyzed the expression of HMGA2 in the human osteosarcoma cell lines MG63, 143B, U2OS, Saos‐2, MNNG/HOS, and KHOS. HMGA2‐specific siRNA and clonogenic assays were then used to determine the effect of HMGA2 inhibition on osteosarcoma cell proliferation, growth, and chemosensitivity. Results: HMGA2 expression was elevated in the osteosarcoma patient specimens and human osteosarcoma cell lines. HMGA2 was differentially expressed in human osteosarcoma cell lines. Specifically, a relatively high expression of HMGA2 was present in KHOS, MNNG/HOS, 143B and a relatively low expression was in MG63, U2OS as well as Saos‐2. HMGA2 expression is correlated with metastasis and shorter overall survival. High HMGA2 expression is an independent predictor of poor osteosarcoma prognosis. There was no significant correlation between HMGA2 expression and the age, gender, or tumor site of the patient. HMGA2 expression is predominantly within the nucleus. The expression of HMGA2 also directly correlated to neoadjuvant chemoresistance. There was a significant reduction of HMGA2 expression in the siRNA transfection group. After the use of siRNA, the proliferation of osteosarcoma cells is decreased and the chemosensitivity of osteosarcoma cells is significantly increased. Conclusion: Our study supports HMGA2 as a potential prognostic biomarker and therapeutic target in osteosarcoma. Abstract : The expression of HMGA2 in osteosarcoma patient tissue samples is evaluated by IHC staining of the TMA.